The rental of Holy Trinity abbey, Lough Cé - Clyne, Miriam (Medieval Lough Cé: History, archaeology and landscape, 2010)
Keywords: lough key

The Annals of Loch Cé: Scribes and Manuscripts - Cunningham, Bernadette (Irish Arts Review, 2009)
Keywords: lough key

Archaeological Excavations at Holy Trinity Abbey Lough Key, Co. Roscommon - Clyne, Miriam (Proceedings of the Royal Irish Academy. Section C: Archaeology, Celtic Studies, History, Linguistics, Literature, 2005)
The excavations at the Premonstratensian abbey on a lake island in the Gaelic-Irish territory of Moylurg are described. The development of the monastery from its foundation c.1220 to its abandonment by the canons c.1606-7 is traced in the structural remains, the occupational levels and the artefacts uncovered. Although the standard claustral plan was envisaged for the monastery, it was apparent from the investigations that only the east range was actually built. During the monastic occupation, the religious community and lay people were buried within the abbey buildings and in two cemeteries outside. The collection of finds provides an insight into the day-to-day activities that were carried out at the abbey. Many of the artefacts were for domestic or agricultural use and were manufactured locally. The excavation revealed evidence that the building to the north of the church was rebuilt following a fire in the fifteenth century. There was also archaeological evidence of the destruction of the east range by another fire and the continued use of the church for burial in the post-dissolution period.
Keywords: lough key

1991:112 - Holy Trinity Abbey, Trinity Island, Roscommon - Clyne, Miriam (Excavations.ie, 1991)
Keywords: lough key

The Annals of Connacht and Loch Cé and the Monasteries of Boyle and Holy Trinity - O'Dwyer, B.W. (Proceedings of the Royal Irish Academy: Archaeology, Culture, History, Literature, 1972)
Keywords: lough key

The Annals of Lough Key (Loch Cé) - O'Flanders, A. (Analecta Praemonstratensia, 1930)
Keywords: lough key

The Annals of Lough Key - Healy, John (The Irish Monthly, 1878)
Keywords: lough key

The annals of Loch Cé : a chronicle of Irish affairs from A.D. 1014 to A.D. 1590 - Hennessy, W.M. (1871)
Keywords: lough key